PEMAKAIAN GAYA BAHASA PADA IKLAN SUSU FORMULA ANAK-ANAK - Ana Rosmiati (Institut Seni Indonesia Surakarta, 2014)
Advertising is a tool to convey the information about a thing or goods. Advertising is usually popularizedthrough a media includes electronic as well as printed media like radio, television, or printed advertising.Advertising is supposed to persuade or influence people to use or utilize the things or goods. Advertising isdesigned by sophisticated technology so that it can be easily accessed by public. The research aims to findthe kinds of language styles in the advertisement of the kid formula milk. The milk consumer in Indonesia isvery high. For the reason, then, the agents of advertisement try to make language style designed by picturesand interesting models in order to influence people to choose the milk. The research uses descriptive qualitativemethod. Descriptive research aims to make a systematic, factual, and accurate description about the facts,characteristics, and the relationship between the researched phenomena. Data source in this research usedocumentation technique. The result is the kinds of language styles used in the advertisement of the kidsformula milk including hyperbola, metonymy, personification, and sinekdok. All of the kinds of languagestyles mostly dominate the advertisement in the kid formula milk.Keywords: advertisement, milk, formula, the kids, language style